An EDS1 heterodimer signalling surface enforces timely reprogramming of immunity genes in Arabidopsis - Deepak D. Bhandari (Nature Portfolio, 2019)
CC and TIR-domain type NLR receptors trigger plant immunity in response to pathogen effectors. Here, Bhandari et al. show that the EP-domain surface of EDS1 heterodimers signals downstream of both receptor types and ensures a rapid transcriptional response in TIR-NLR immunity to bacteria.